2022
DOI: 10.3389/fgene.2021.768209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on the Ruminal Epithelial Barrier of Dairy Cows Revealed by Micromorphological Observation and Transcriptomic Analysis

Abstract: Heat stress (HS) alters the rumen fermentation of dairy cows thereby affecting the metabolism of rumen papillae and thus the epithelial barrier function. The aim of the present study was to investigate if HS damages the barrier function of ruminal epithelia. Eight multiparous Holstein dairy cows with rumen cannula were randomly equally allocated to two replicates (n = 4), with each replicate being subjected to heat stress or thermal neutrality and pair-feeding in four environmental chambers. Micromorphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Our findings from the micromorphological analysis that heat stress aggravates cuticle shedding and contributes to the disruption of the physical barrier of the rumen epithelium are consistent with those of a previous study [4]. Heat stress caused detrimental alterations to the tissue structure of the rumen epithelium and particularly resulted in cuticle degradation.…”
Section: Effects Of Niacin On Gene Expression and Tissue Structure Of...supporting
confidence: 91%
See 1 more Smart Citation
“…Our findings from the micromorphological analysis that heat stress aggravates cuticle shedding and contributes to the disruption of the physical barrier of the rumen epithelium are consistent with those of a previous study [4]. Heat stress caused detrimental alterations to the tissue structure of the rumen epithelium and particularly resulted in cuticle degradation.…”
Section: Effects Of Niacin On Gene Expression and Tissue Structure Of...supporting
confidence: 91%
“…Heat stress disrupts the metabolism of rumen papillae and alters the rumen fermentation of the beef cattle, which subsequently affects the epithelial barrier function [4]. Micromorphological observations have suggested that heat stress exacerbates the exfoliation of the stratum corneum, leading to the destruction of the rumen epithelium's physical barrier [4]. Therefore, ensuring the homeostasis of ruminal epithelial barrier function is crucial for the health of ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics such as Lactobacillus plantarum MB452 also enhance the barrier function of the rumen epithelium by increasing the expression of tight junction genes [68]. Heat stress affects the rumen epithelial barrier negatively to some extent but does not completely disrupt it, due to the upregulation of heat shock proteins [69]. In essence, the strength of the physical barrier of the rumen is intricately linked with the microbes and immune cells in the rumen.…”
Section: Barrier Functionmentioning
confidence: 99%
“…Under HS circumstances, the acetate-producing bacteria Actinobacteria and Acetobacter shrank (Kim et al 2022). Heat stress alters the rumen fermentation of dairy cows, affecting the rumen papillae's metabolism and, thus, the epithelial barrier function (Guo et al 2022). Zhao et al (2019) reported that heat stress resulted in the reduction of pH and acetate levels in the rumen; however, heat stress resulted in an increase in lactate levels in the rumen.…”
Section: Rumen Fermentationmentioning
confidence: 99%